2019
DOI: 10.1002/jbmr.3871
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose TGF-β1 Impairs Mesenchymal Stem Cell–Mediated Bone Regeneration via Bmp2 Inhibition

Abstract: Transforming growth factor‐β1 (TGF‐β1) is a key factor in bone reconstruction. However, its pathophysiological role in non‐union and bone repair remains unclear. Here we demonstrated that TGF‐β1 was highly expressed in both C57BL/6 mice where new bone formation was impaired after autologous bone marrow mesenchymal stem cell (BMMSC) implantation in non‐union patients. High doses of TGF‐β1 inhibited BMMSC osteogenesis and attenuated bone regeneration in vivo. Furthermore, different TGF‐β1 levels exhibited opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 59 publications
(85 reference statements)
0
51
0
Order By: Relevance
“…In vitro studies have shown that TGF-β1 inhibits stem cell osteogenesis. [76][77][78] We have also shown that in vitro supplementation of TGF-β1, at a concentration similar to that in plasma, almost completely blocked BMP-7-induced osteogenesis in cultures of MDSCs, 65 muscle resident stem cells that have been considered as putative HO cell source in vivo. 40 This finding confirms that TGF-β1 may play an inhibitory role on MDSC osteogenesis, which supports our systemic osteogenic protective factor/differentiation threshold hypothesis (Figure 3).…”
Section: Macrophag E Phenot Ype Modul Ation and Homentioning
confidence: 65%
See 4 more Smart Citations
“…In vitro studies have shown that TGF-β1 inhibits stem cell osteogenesis. [76][77][78] We have also shown that in vitro supplementation of TGF-β1, at a concentration similar to that in plasma, almost completely blocked BMP-7-induced osteogenesis in cultures of MDSCs, 65 muscle resident stem cells that have been considered as putative HO cell source in vivo. 40 This finding confirms that TGF-β1 may play an inhibitory role on MDSC osteogenesis, which supports our systemic osteogenic protective factor/differentiation threshold hypothesis (Figure 3).…”
Section: Macrophag E Phenot Ype Modul Ation and Homentioning
confidence: 65%
“…In vitro studies have shown that TGF‐β1 inhibits stem cell osteogenesis 76‐78 . We have also shown that in vitro supplementation of TGF‐β1, at a concentration similar to that in plasma, almost completely blocked BMP‐7‐induced osteogenesis in cultures of MDSCs, 65 muscle resident stem cells that have been considered as putative HO cell source in vivo 40 .…”
Section: Macrophage Phenotype Modulation and Homentioning
confidence: 71%
See 3 more Smart Citations